Hybrid livelihoods: Maize and agrarian transformation in Southeast Asia's uplands - Belton, Ben; Fang, Peixun (Elsevier, 2022)
Hybrid maize farming has boomed across upland Southeast Asia in the past three decades. Recent studies suggest that the boom has resulted in diverse outcomes across countries. In Thailand, Vietnam, and Laos, the introduction of hybrid maize has often initially been linked to rising incomes and living standards, with little loss or concentration of landholdings. In contrast, recent studies from Myanmar argue that exploitative trader-farmer credit relations are driving rapid agrarian differentiation and dispossession. We analyze patterns of agrarian change associated with hybrid maize farming in southern Shan State, Myanmar, using data from a representative survey of 1562 rural households. Widespread farmer engagement in maize cultivation has contributed to deepening petty commodity production and some economic differentiation, but with little dispossession or negative impacts on food security. Credit provision by traders may benefit some larger farmers but does not actively penalize smaller producers. Hybrid maize is a ‘moderate risk, moderate reward’ crop that households integrate strategically into a broader patchwork of subsistence farming, higher risk cash crop production, and a growing mix of off-farm activities. Employment in non-farm enterprises, salaried work, and migration have significant potential to modify trajectories of differentiation associated with agriculture.